COMPARISON OF BALB/C MICE IMMUNE RESPONSE WHICH HAS BEEN INDUCED WITH DIFFERENT RABIES VACCINE - Ilham Yusuf Bahniar Putera; I Gusti Ayu Agung Suartini; Tri Komala Sari (Buletin Veteriner Udayana, 2026)
Rabies is a fatal zoonotic disease that remains incurable, making vaccination the primary strategy for prevention in veterinary and human public health. Although multiple commercial rabies vaccines are widely used, comparative data on their immunogenicity are limited and often inconsistent. This study evaluated and compared the humoral and cellular immune responses induced by three commercially available rabies vaccine brands using a BALB/c mouse model. Ten 20-week-old female BALB/c mice were allocated into treatment groups and immunized accordingly. Blood samples were collected at week 0 (pre-vaccination), week 2, and week 4 post-vaccination to determine specific anti-rabies antibody titers using enzyme-linked immunosorbent assay (ELISA). At the end of the study, spleens were harvested for histopathological examination with hematoxylin–eosin staining to assess cellular immune responses. Antibody titers were analyzed using analysis of variance (ANOVA). All three vaccines induced a significant and comparable increase in antibody titers up to two weeks post-vaccination, with no statistically significant differences among brands. By week 4, a decline in antibody levels was observed across all groups. Histopathological analysis revealed similar activation of cellular immunity among vaccines, characterized by lymphoid proliferation and plasma cell activity, without notable inter-group differences. In conclusion, the three commercial rabies vaccines demonstrated equivalent immunogenicity in inducing both humoral and cellular immune responses in BALB/c mice. These findings suggest that no single vaccine brand was superior, and that rabies vaccination strategies should prioritize operational factors such as schedule adherence, booster administration, and proper vaccination techniques rather than brand selection.